Lathrolestes verticalis Brischke 1871 - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes verticalis (Brischke, 1871) Figs. 41, 120–123. Perilissus verticalis Brischke, 1871: 71. Type lost. Type locality: Poland. Perilissus abdominalis Brischke, 1878: 74. Type lost. Type locality: Poland. Lathrolestus marginatus Thomson, 1883: 917. Holotype ♂, MZLU [examined]. Type locality: Sweden (Skåne, Lund). Material. 1♀, DENMARK, Jutland, Sønderborg, ZMUC; 5♀, 7♂, DENMARK, leg Schiødte, ZMUC; 1♂, FINLAND, Uusikaupunki (“Nystad”), leg. Hellen, MZH; 1♀, FINLAND, Åboland, Pernå, 9.viii.1944, leg Å.Nordström, MZH; 7♀, GENMANY, Northern Germany, ex. Metallus pumilus, xi.1970, leg H.Pschorn-Walcher, SMF; 1♂, RUSSIA, Republic of Karelia, Sortavala, “L.v. Essen”, “3461”, MZH; 1♂, RUSSIA, Leningrad Oblast, Boksitogorsky reg., 20 km S Boksitogorsk, Rgusha riv., viii.2002, leg. A.Reshchikov, NHRS; 2♀, SWEDEN, Skåne, 1907, leg. A. Roman, NHRS; 2♀, SWEDEN, Halland, viii.1922, leg. A. Roman, NHRS; 2♀, 1♂, SWEDEN, Stockholm, leg. C. Boheman, NHRS; 1♀, SWEDEN, Gotland, Visby, Själsö, N57°41.582´E18°21.530´, 18m., 30.v.–vii. 09.2013, Malaise trap, leg. Alexey Reshchikov & Niklas Apelqvist, NHRS; 1♀, SWEDEN, Småland, Torsås kommun, Söderåkra, Påboda. Malaise trap in garden N625636, E151637 (=TrapID 2046), 2008. viii.01–2008. viii.16 (=coll. event ID 2056), leg. SMTP, NHRS; 2♀, SWEDEN, Småland, Torsås kommun, Söderåkra, Påboda. Malaise trap in garden N625636, E151637 (=TrapID 2046) 2008. vii.16–2008. viii.01 (=coll. event ID 2055), leg. SMTP, SMTP; 3♀, SWEDEN, Sm, Torsås kommun, Söderåkra, Påboda. Malaise trap in garden N625636, E151637 (=TrapID 2046)2008. viii.16–2008. ix.01 (=coll. event ID 2057), leg. SMTP, SMTP; 1♀, 3♂, SWEDEN, Skåne, Klippans kommun, Skäralid, valley below northern Lierna, Rich beech forest. N56°01.633´E13°13.406´(= TrapID 37), 14.vii–06.viii.2004 (=coll. event ID 834), leg. SMTP, NHRS; 1♂, SWEDEN, Småland, Nybro kommun, Bäckebo, Grytsjöns naturreservat, Old aspen forest in boulder terrain, N6310596 E1518027 (=TrapID 1000), 02.viii–13.viii.2005 (=coll. event ID 1359), leg. SMTP, SMTP; 2♂, ...